Internalizing Local Wisdom Through Live-In Program and History Learning - Levia Chessiagi; Leli Yulifar (Universitas Negeri Medan, 2026)
This study examines the internalization of local wisdom values through a live-in program and the reinforcement of these values through history learning. The study was motivated by concerns that globalization has increasingly displaced locally grounded value systems among younger generations. This study uses a qualitative approach with ethnographic methods, the research involved 10th grade students of SMA Santo Aloysius Bandung who participated in a live-in program in Cigugur, Kuningan, West Jawa, Indonesia. Data were collected through participant observation, interviews, reflective journals, and field notes, and analyzed using Wolcott’s stages of ethnographic analysis: description, analysis, and interpretation, with Kolb’s Experiential Learning Theory serving as the interpretive framework. The findings indicate that direct immersion in the Cigugur Community enabled students to experience tolerance and gotong royong (mutual cooperation) as lived social practices. Post live-in history learning further strengthened the internalization process by connecting students’ experiences with the historical and cultural context of the community. The integration of community immersion and reflective history learning offers a meaningful approach to strengthening local wisdom values among younger generations in the era of globalization..